Phosphate-based positive electrode active material and preparation method and application thereof

By doping boron nitrid hybrid crystals, niobium and titanate in the phosphate positive electrode material, the problem of low conductivity of the phosphate positive electrode material is solved, the circulation and rate performance of the battery is improved, and the manufacturing temperature and cost are reduced.

CN119517974AActive Publication Date: 2025-02-25SHANGHAI LING FRANCIUM NEW ENERGY TECH CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510090869.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-02-25
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The low ion and electron conductivity of existing phosphate cathode materials limits the performance of battery performance, especially at high magnification and low temperature conditions.

Method used

By doping boron-nitrid hybrid crystals into the phosphate positive electrode material, a composite material is formed, the ion migration distance is shortened, the conductivity is improved, and the internal resistance of the battery is reduced through niobium and titanate doping.

Benefits of technology

The electrochemical properties of the cathode material are significantly improved, especially the cyclic properties and rate performance, and the temperature and manufacturing costs during the manufacturing process are reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a phosphate-based positive electrode active material and a preparation method and application thereof, and belongs to the field of secondary battery materials. Wherein the molecular formula of the phosphate-based positive electrode active material is LaFex1Nbx2Mx3 (PO4) y (P2O7) z (TiO3) e / BN (at) C, and the boron-nitrogen doped carbon layer forms a conductive coating layer on the surface of the LaFex1Nbx2Mx3 (PO4) y (P2O7) z (TiO3) e. By mass fraction, the boron-nitrogen doped carbon layer accounts for 1-5% of the positive electrode active material, and the boron-nitrogen element accounts for 0.05-0.2% of the coating layer. The boron-nitrogen compound can improve the electrochemical performance of the positive electrode active material, reduce the temperature in the manufacturing process and ensure the capacity of the active material; in addition, Nb doping can reduce the internal resistance of the battery and improve the cycling stability and the rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of secondary batteries, and in particular to a phosphate-based positive electrode active material for secondary batteries, and a preparation method and application thereof. Background Art

[0002] As secondary energy storage devices, lithium / sodium ion batteries play an important role in new energy vehicles, mobile smart devices, large-scale energy storage and other fields. With the rapid expansion of new energy vehicles and large-scale energy storage markets, the demand for power / energy storage batteries is also rapidly expanding, and the research and development of high-performance batteries and materials is extremely important. Phosphates have the advantages of being environmentally friendly, low cost, and stable structure. They have been used in the fields of lithium-ion batteries and sodium-ion batteries, and the market demand is also growing continuously.

[0003] Currently, commercialized phosphate cathode materials such as lithium iron phosphate, lithium iron manganese phosphate, sodium iron pyrophosphate, sodium iron phosphate, and sodium vanadium phosphate have been widely used in the field of power / energy storage batteries. However, although phosphate cathode materials have stable structures and long cycle life, phosphate-based cathode materials have low ion and electronic conductivity, which greatly limits the performance of batteries, especially high-rate and low-temperature performance. How to improve the electrochemical performance of phosphate cathode materials is one of the hot research directions in the industry.

[0004] Based on the fact that metal organic framework materials are a new type of porous crystalline hybrid material, they have the characteristics of adjustable structure, long-range order and controllable porosity, and can be used as a precursor to prepare a structure-controllable, high-performance electrode material with phosphate, which can greatly improve the electrochemical properties of the positive electrode material. In view of this, the present invention provides a technical solution to solve the insufficient electrochemical performance of phosphate electrode materials. Summary of the invention

[0005] One of the purposes of the present invention is to provide a phosphate positive electrode active material, and to prepare a composite phosphate positive electrode material by doping with boron-nitrogen hybrid crystals, effectively shortening the ion migration distance, improving the ion and electronic conductivity of the positive electrode material, and improving the electrochemical properties of the positive electrode active material, especially the cycle performance and rate performance. Boron and organic ligands form a boron-containing hybrid crystal material and a composite phosphate positive electrode material. The material has a high content of boron and nitrogen elements, and the contained BH functional groups have good reducibility, which is beneficial to the reduction of transition metal ions in the phosphate positive electrode material to a low-valent state, and reduces the temperature in the manufacturing process of the positive electrode material, thereby reducing the manufacturing cost. In addition, niobium and titanate-doped phosphate-based positive electrode materials can reduce the internal resistance of the battery, which is of great significance for the design of high-rate power batteries.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A phosphate electrode active material with the chemical general formula of L for the active material a Fe x1 Nb x2 M x3 (PO4) y (P2O7) z (TiO3) e / BN@C, where the boron and nitrogen doped carbon layer forms a conductive coating layer on the surface of L a Fe x1 Nb x2 M x3 (PO4) y (P2O7) z (TiO3) e ; wherein 0.5 < a ≤ 1.1, 0 < x1 < 1, 0 < x2 < 0.05, 0 < x3 < 1, 0 < y ≤ 1, 0 ≤ z ≤ 1, 0 < e ≤ 0.05, L is one or both of Na and Li, and M is one or more of Mn, Ni, V, Ti, Mg, Cu, Zn, Zr. Preferably, 0.8 < a ≤ 1, 0 < x1 < 1, 0 < x2 < 0.03, 0 < x3 < 0.8, 0 < y ≤ 1, 0 ≤ z ≤ 0.8, 0 < e ≤ 0.05.

[0008] Among them, calculated by mass fraction, the content of the boron and nitrogen doped carbon layer on the surface of the positive electrode active material accounts for 1 to 5% or less of the positive electrode active material, and the content of boron and nitrogen elements accounts for 0.05 to 0.2% of the coating layer.

[0009] The second object of the present invention is to provide a preparation method of the above-mentioned phosphate electrode active material, comprising the following steps:

[0010] S1. Add sodium borohydride or lithium borohydride, a nitrogen-containing organic precursor, and glucose into a flask, reflux and stir and heat at 100 - 250 °C for 1 - 5 h under nitrogen conditions, and cool it to room temperature to obtain carbon source powder A;

[0011] S2. Select several of carbon source powder A, L source compound, Fe source compound, M source compound, Nb source compound, and phosphorus source compound as raw materials according to the structure of the phosphate active material, and weigh an appropriate amount of the above raw materials for premixing to obtain a premixed powder;

[0012] S3. Add the premixed powder, solvent, and dispersant into a nano sand mill for ball milling to obtain a slurry, and the primary particle size range of the slurry is 100 - 400 nm;

[0013] S4, spray-drying and granulating the slurry to obtain a precursor powder; then pre-sintering the precursor powder under an inert atmosphere, cooling it, and mixing it evenly with sodium metatitanate or lithium metatitanate by double planetary mechanical ball milling, sintering the evenly mixed powder under an inert atmosphere, and cooling it to obtain the composite phosphate positive electrode active material L coated with the boron-nitrogen doped carbon layer. a Fe x1 Nb x2 M x3 (PO4) y (P2O7) z (TiO3) e / BN@C.

[0014] Wherein, in step S2, the L source compound is selected from one or more of sodium carbonate, sodium hydroxide, sodium oxalate, sodium nitrate, lithium carbonate, lithium hydroxide, lithium oxalate, and lithium nitrate; the Fe source compound is selected from one or more of carbonates, oxides, nitrates, and oxalates; the M source compound is selected from one or more of carbonates, oxides, nitrates, and oxalates; the Nb source compound is selected from one or more of niobium pentoxide, niobium tetroxide, niobium trioxide, niobium oxide, niobium sulfide, niobium pentachloride, niobium tetrachloride, and niobium nitride; the phosphorus source compound is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; the nitrogen-containing organic precursor is selected from one or more of 2-methylimidazole, 2-ethylimidazole, 3-propylimidazole, and imidazole.

[0015] Among them, in step S3, the dispersant is selected from one or more of ammonium polyacrylate, polyvinyl pyrrolidone, and polyethylene glycol; the solvent is deionized water; the mass ratio of the premixed powder to the solvent is 1:(2~5); the mass of the dispersant is 0.1~2% of the mass of the solvent; and the ball milling time is 5~15h.

[0016] Among them, in step S4, the inert atmosphere is nitrogen or argon; the particle size of the sodium metatitanate or lithium metatitanate is 0.2~0.6µm; the pre-sintering temperature is 300~400℃, and the sintering time is 1~3h; the sintering temperature is 500~800℃, and the sintering time is 5~15h.

[0017] Wherein, in step S4, calculated by mass fraction, the boron-nitrogen doped carbon layer accounts for 1-5% of the active material, and the boron-nitrogen element content accounts for 0.05-0.2% of the coating layer.

[0018] The third object of the present invention is to provide a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material described above.

[0019] The fourth object of the present invention is to provide a sodium ion battery or a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator separated between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet described above.

[0020] Beneficial effects:

[0021] The boron-nitrogen composite phosphate-based positive electrode active material provided by the present invention improves the electrochemical performance of the positive electrode material by compounding the boron-nitrogen compound with the phosphate-based active material. The composite material has a certain content of boron and nitrogen elements, and the contained BH functional group has good reducibility, which is conducive to the reduction of transition metal ions in the phosphate positive electrode material to a low valence state, reduces the temperature in the manufacturing process of the positive electrode material, and reduces the crystallization temperature. It is of great significance to the phosphate-based active material for sodium ion batteries, because too high a crystallization temperature will cause the phosphate-based positive electrode material to generate a phosphate-based iron ore structure positive electrode material without electrochemical activity, resulting in an extremely low capacity of the active material, so a precursor rich in boron-nitrogen compounds can improve this defect well. In addition, during the heat treatment process, the hybrid crystalline material is cracked into a carbon layer rich in boron and nitrogen elements to wrap the phosphate positive electrode material, effectively improving the shortcomings of the poor ion and electronic conductivity of the phosphate positive electrode material, and improving the electrochemical performance of the positive electrode active material. In addition, Nb doping can reduce the internal resistance of the battery, improve cycle stability and rate performance. DETAILED DESCRIPTION

[0022] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.

[0023] Example 1

[0024] A composite phosphate positive electrode active material with the molecular formula of NaFe 0.7 Nb 0.01 Mg 0.01 (PO4) 0.5 (P2O7) 0.25 (TiO3) 0.01 / BN@C.

[0025] The preparation method of the positive electrode active material comprises the following steps:

[0026] S1. Sodium borohydride, 2-methylimidazole (mass ratio 1:5) and glucose were added into a flask, heated under reflux stirring at 220°C for 2 h under nitrogen, and cooled to room temperature to obtain carbon source powder A.

[0027] S2. Weigh carbon source powder A, sodium carbonate, ferrous oxalate, niobium oxide, magnesium oxide and ammonium dihydrogen phosphate, and premix them to obtain a premixed powder; wherein the molar ratio of Na:Fe:Nb:Mg:P is 1:0.7:0.01:0.01:1.

[0028] S3. The premixed powder, deionized water and ammonium polyacrylate (ammonium polyacrylate is 0.2% of the mass of deionized water) in a mass ratio of 1:2 are added into a nano sand mill for high-energy ball milling for 8 hours to obtain a slurry with a primary particle size of about 200 nm.

[0029] S4, spray-drying and granulating the slurry to obtain a precursor powder; then pre-sintering the precursor powder at 350°C for 2 hours in a nitrogen atmosphere, and mixing it with sodium metatitanate by double planetary mechanical ball milling after cooling, sintering the mixed powder at 550°C for 10 hours in a nitrogen atmosphere, and naturally cooling it to room temperature to obtain a precursor powder with a molecular formula of NaFe 0.7 Nb 0.01 Mg 0.01 (PO4) 0.5 (P2O7) 0.25 (TiO3) 0.01 / BN@C is a positive electrode active material. In terms of mass fraction, the boron and nitrogen doped carbon layer accounts for 2% of the active material, and the boron and nitrogen content accounts for 0.1% of the coating layer.

[0030] The positive electrode active material obtained above is applied to positive electrode sheets and button batteries, and the preparation process is as follows:

[0031] Positive electrode sheet: 1.9 g of the obtained positive electrode active material was weighed, 0.05 g of carbon black and 0.05 g of polyvinylidene fluoride dissolved in N, N'-methylpyrrolidone were added, and the mixture was homogenized and coated on aluminum foil to prepare a positive electrode sheet.

[0032] Button cell: In a glove box with argon atmosphere, 2032 button cells were assembled with metallic sodium as the counter electrode, glass fiber as the separator, and 1 M / NaPF6 / PC:EMC:EC (volume ratio 1:1:1) as the electrolyte.

[0033] Example 2

[0034] A composite phosphate positive electrode active material with the molecular formula Li 0.1 Na 0.9 Fe 0.7 Nb 0.01 Mg 0.01 (PO4) 0.5 (P2O7) 0.25 (TiO3) 0.01 / BN@C.

[0035] The preparation method of the positive electrode active material comprises the following steps:

[0036] S1. Sodium borohydride, 2-ethylimidazole (mass ratio 1:5) and glucose were added into a flask, heated under reflux stirring at 180°C for 5 h under nitrogen, and cooled to room temperature to obtain carbon source powder A.

[0037] S2. Weigh carbon source powder A, lithium carbonate, sodium carbonate, ferrous oxalate, niobium oxide, magnesium oxide and diammonium phosphate and premix them to obtain a premixed powder; wherein the molar ratio of Li:Na:Fe:Nb:Mg:P is 0.1:0.9:0.7:0.01:0.01:1.

[0038] S3. The premixed powder, deionized water and ammonium polyacrylate (ammonium polyacrylate is 0.5% of the mass of deionized water) in a mass ratio of 1:2 are added into a nano sand mill for high-energy ball milling for 15 hours to obtain a slurry with a primary particle size of about 300 nm.

[0039] S4, spray-drying and granulating the slurry to obtain a precursor powder; then pre-sintering the precursor powder at 300°C for 3 hours in a nitrogen atmosphere, and mixing it with sodium metatitanate by double planetary mechanical ball milling after cooling, sintering the mixed powder at 500°C for 15 hours in a nitrogen atmosphere, and naturally cooling it to room temperature to obtain a precursor powder with a molecular formula of Li 0.1 Na 0.9 Fe 0.7 Nb 0.01 Mg 0.01 (PO4) 0.5 (P2O7) 0.25 (TiO3) 0.01 / BN@C is a positive electrode active material. In terms of mass fraction, the boron and nitrogen doped carbon layer accounts for 1.8% of the active material, and the boron and nitrogen content accounts for 0.05% of the coating layer.

[0040] The positive electrode active material obtained above is applied to positive electrode sheets and button batteries, and the preparation process is as follows:

[0041] Positive electrode sheet: 1.9 g of the obtained positive electrode active material was weighed, 0.05 g of carbon black and 0.05 g of polyvinylidene fluoride dissolved in N, N'-methylpyrrolidone were added, and the mixture was homogenized and coated on aluminum foil to prepare a positive electrode sheet.

[0042] Button cell: In a glove box with argon atmosphere, 2032 button cells were assembled with metallic sodium as the counter electrode, glass fiber as the separator, and 1 M / NaPF6 / PC:EMC:EC (volume ratio 1:1:1) as the electrolyte.

[0043] Example 3

[0044] A composite phosphate positive electrode active material with the molecular formula LiFe 0.38 Nb 0.02 Mn 0.6 PO4(TiO3) 0.01 / BN@C.

[0045] The preparation method of the positive electrode active material comprises the following steps:

[0046] S1. Add lithium borohydride, 2-methylimidazole (mass ratio 1:5) and glucose into a flask, reflux and stir at 200°C for 5 h under nitrogen, and cool to room temperature to obtain carbon source powder A.

[0047] S2. Weigh carbon source powder A, lithium carbonate, ferrous oxalate, niobium oxide, manganese oxalate and ammonium dihydrogen phosphate, and premix them to obtain a premixed powder; wherein the molar ratio of Li:Fe:Nb:Mn:P is 1:0.38:0.02:0.6:1.

[0048] S3. The premixed powder, deionized water and ammonium polyacrylate (ammonium polyacrylate is 0.5% of the mass of deionized water) in a mass ratio of 1:2 are added into a nano sand mill for high-energy ball milling for 10 hours to obtain a slurry with a primary particle size of about 150 nm.

[0049] S4, spray-drying and granulating the slurry to obtain a precursor powder; then pre-sintering the precursor powder at 350°C for 3 hours in a nitrogen atmosphere, and mixing it with lithium metatitanate by double planetary mechanical ball milling after cooling, sintering the mixed powder at 700°C for 12 hours in a nitrogen atmosphere, and naturally cooling it to room temperature to obtain a LiFe 0.38 Nb 0.02 Mn 0.6 PO4(TiO3) 0.01 / BN@C is a positive electrode active material. In terms of mass fraction, the boron and nitrogen doped carbon layer accounts for 3% of the active material, and the boron and nitrogen content accounts for 0.15% of the coating layer.

[0050] The positive electrode active material obtained above is applied to positive electrode sheets and button batteries, and the preparation process is as follows:

[0051] Positive electrode sheet: 1.9 g of the obtained positive electrode active material was weighed, 0.05 g of carbon black and 0.05 g of polyvinylidene fluoride dissolved in N, N'-methylpyrrolidone were added, and the mixture was homogenized and coated on aluminum foil to prepare a positive electrode sheet.

[0052] Button cell: In a glove box with argon atmosphere, 2032 button cells were assembled with metallic lithium as the counter electrode, glass fiber as the separator, and 1 M / LiPF6 / PC:EMC:EC (volume ratio 1:1:1) as the electrolyte.

[0053] Example 4

[0054] A composite phosphate positive electrode active material with the molecular formula LiFe 0.98 Nb 0.01 Mg 0.01 PO4(TiO3) 0.01 / BN@C.

[0055] The preparation method of the positive electrode active material comprises the following steps:

[0056] S1. Add lithium borohydride, 2-methylimidazole (mass ratio 1:5) and glucose into a flask, reflux and stir and heat at 200°C for 3 h under nitrogen, and cool to room temperature to obtain carbon source powder A.

[0057] S2. Weigh carbon source powder A, lithium carbonate, ferrous oxalate, niobium oxide, magnesium oxide and diammonium phosphate and premix them to obtain a premixed powder; wherein the molar ratio of Li:Fe:Nb:Mg:P is 1:0.98:0.01:0.01:1.

[0058] S3. The premixed powder, deionized water and ammonium polyacrylate (ammonium polyacrylate is 0.4% of the mass of deionized water) in a mass ratio of 1:2 are added into a nano sand mill for high-energy ball milling for 10 hours to obtain a slurry with a primary particle size of about 250 nm.

[0059] S4, spray-drying and granulating the slurry to obtain a precursor powder; then pre-sintering the precursor powder at 300°C for 3 hours in a nitrogen atmosphere, and mixing it with lithium metatitanate by double planetary mechanical ball milling after cooling, sintering the mixed powder at 700°C for 8 hours in a nitrogen atmosphere, and naturally cooling it to room temperature to obtain a precursor powder with a molecular formula of LiFe 0.98 Nb 0.01 Mg 0.01 PO4(TiO3) 0.01 / BN@C is a positive electrode active material. In terms of mass fraction, the boron and nitrogen doped carbon layer accounts for 2% of the active material, and the boron and nitrogen content accounts for 0.1% of the coating layer.

[0060] The positive electrode active material obtained above is applied to positive electrode sheets and button batteries, and the preparation process is as follows:

[0061] Positive electrode sheet: 1.9 g of the obtained positive electrode active material was weighed, 0.05 g of carbon black and 0.05 g of polyvinylidene fluoride dissolved in N, N'-methylpyrrolidone were added, and the mixture was homogenized and coated on aluminum foil to prepare a positive electrode sheet.

[0062] Button cell: In a glove box with argon atmosphere, 2032 button cells were assembled with metallic lithium as the counter electrode, glass fiber as the separator, and 1 M / LiPF6 / PC:EMC:EC (volume ratio 1:1:1) as the electrolyte.

[0063] Example 5

[0064] The difference from Example 1 is that the content of each raw material of the positive electrode active material is changed. The amount of sodium metatitanate is changed. The molecular formula of the positive electrode active material for sodium ion battery obtained is NaFe 0.7 Nb 0.01 Mg 0.01 (PO4) 0.5 (P2O7) 0.25 (TiO3) 0.05 / BN@C.

[0065] The rest is the same as in Example 1 and will not be described again here.

[0066] Example 6

[0067] The difference from Example 1 is the content of each raw material of the positive electrode active material, wherein the molar ratio of Na:Fe:Nb:Mg:P is 1.05:0.75:0.01:0.01:1, and the molecular formula of the positive electrode active material for the obtained sodium ion battery is Na 1.05 Fe 0.75 Nb 0.01 Mg 0.01 (PO4) 0.5 (P2O7) 0.25 (TiO3) 0.01 / BN@C.

[0068] The rest is the same as in Example 1 and will not be described again here.

[0069] Example 7

[0070] Different from Example 1, the boron and nitrogen doped carbon layer accounts for 5% of the active material, and the boron and nitrogen content accounts for 0.1% of the coating layer.

[0071] The rest is the same as in Example 1 and will not be described again here.

[0072] Example 8

[0073] The difference from Example 3 is the content of each raw material of the positive electrode active material, wherein the molar ratio of Li:Fe:Nb:Mn:P is 1:0.26:0.04:0.7:1, and the molecular formula of the positive electrode active material for the obtained sodium ion battery is LiFe 0.26 Nb 0.04 Mn 0.7 PO4(TiO3) 0.01 / BN@C.

[0074] The rest is the same as in Example 3 and will not be described again here.

[0075] Example 9

[0076] The difference from Example 4 is the content of each raw material of the positive electrode active material, wherein the molar ratio of Li:Fe:Nb:Mg:P is 1:0.96:0.02:0.02:1, and the molecular formula of the positive electrode active material for the obtained sodium ion battery is LiFe 0.96 Nb 0.02 Mg 0.02 PO4(TiO3) 0.01 / BN@C

[0077] The rest is the same as in Example 4 and will not be described again here.

[0078] Comparative Example 1

[0079] The difference from Example 1 is that the powder A in the raw material for preparing the positive electrode active material contains only glucose. The molecular formula of the positive electrode active material in this comparative example is NaFe 0.7 Nb 0.01 Mg 0.01 (PO4) 0.5 (P2O7) 0.25 (TiO3) 0.01 / C.

[0080] The rest is the same as in Example 1 and will not be described again here.

[0081] Comparative Example 2

[0082] The difference from Example 1 is the arrangement of the positive electrode active material. The molecular formula of the positive electrode active material in this comparative example is NaFe 0.7 Nb 0.01 Mg 0.01 (PO4) 0.5 (P2O7) 0.25 / BN@C.

[0083] The rest is the same as in Example 1 and will not be described again here.

[0084] Comparative Example 3

[0085] The difference from Example 1 is the arrangement of the positive electrode active material. The molecular formula of the positive electrode active material in this comparative example is NaFe 0.7 (PO4) 0.5 (P2O7) 0.25 / C.

[0086] The rest is the same as in Example 1 and will not be described again here.

[0087] Comparative Example 4

[0088] Different from Example 1, the boron and nitrogen doped carbon layer accounts for 8% of the active material, and the boron and nitrogen content accounts for 0.1% of the coating layer.

[0089] The rest is the same as in Example 1 and will not be described again here.

[0090] Comparative Example 5

[0091] Different from Example 1, the boron and nitrogen doped carbon layer accounts for 2% of the active material, and the boron and nitrogen content accounts for 0.5% of the coating layer.

[0092] The rest is the same as in Example 1 and will not be described again here.

[0093] The button batteries obtained in the above Examples 1 to 11 and Comparative Examples 1 to 5 were tested for cycle performance and rate performance in the 2.0 to 4.2 V charge and discharge range.

[0094] The cycle performance test was carried out on the Land battery tester with a test voltage range of 2.0-4.2V, and the battery's 0.1C first discharge capacity in grams, 10C capacity retention rate, and capacity retention rate after 100 cycles at 1C rate were recorded.

[0095] The test results are shown in Table 1

[0096] Table 1

[0097] Serial number Positive electrode active material Boron-nitrogen doped carbon layer accounts for the mass ratio of active materials / % Boron and nitrogen content in the coating layer mass ratio / % First discharge capacity mAh / g 10C capacity retention rate / % Capacity retention after 100 cycles / % Example 1 <![CDATA[NaFe 0.7 Nb 0.01 Mg 0.01 (PO4) 0.5 (P2O7) 0.25 (TiO3) 0.01 / BN@C]]> 2 0.1 103 91 97 Example 2 <![CDATA[Li 0.1 So 0.9 Feb 0.7 No 0.01 Mg 0.01 (PO4) 0.5 (P2O7) 0.25 (TiO3) 0.01 / BN@C]]> 1.8 0.05 105 90 98 Example 3 <![CDATA[LiFe 0.38 Nb 0.02 Mn 0.6 PO4(TiO3) 0.01 / BN@C]]> 3 0.15 151 86 96 Example 4 <![CDATA[LiFe 0.98 Nb 0.01 Mg 0.01 PO4(TiO3) 0.01 / BN@C]]> 2 0.1 156 88 99 Example 5 <![CDATA[NaFe 0.7 Nb 0.01 Mg 0.01 (PO4) 0.5 (P2O7) 0.25 (TiO3) 0.05 / BN@C]]> 2 0.1 100 92 95 Example 6 <![CDATA[Na 1.05 Fe 0.75 Nb 0.01 Mg 0.01 (PO4) 0.5 (P2O7) 0.25 (TiO3) 0.01 / BN@C]]> 2 0.1 102 90 96 Example 7 <![CDATA[NaFe 0.7 Nb 0.01 Mg 0.01 (PO4) 0.5 (P2O7) 0.25 (TiO3) 0.01 / BN@C]]> 5 0.1 102 88 94 Example 8 <![CDATA[LiFe 0.26 Nb 0.04 Mn 0.7 PO4(TiO3) 0.01 / BN@C]]> 3 0.15 150 85 97 Example 9 <![CDATA[LiFe 0.96 Nb 0.02 Mg 0.02 PO4(TiO3) 0.01 / BN@C]]> 2 0.1 155 87 98 Comparative Example 1 <![CDATA[NaFe 0.7 Nb 0.01 Mg 0.01 (PO4) 0.5 (P2O7) 0.25 (TiO3) 0.01 / C]]> 2 0 99 79 89 Comparative Example 2 <![CDATA[NaFe 0.7 Nb 0.01 Mg 0.01 (PO4) 0.5 (P2O7) 0.25 / BN@C]]> 2 0.1 97 83 84 Comparative Example 3 <![CDATA[NaFe 0.7 (PO4) 0.5 (P2O7) 0.25 / C]]> 2 0 98 78 85 Comparative Example 4 <![CDATA[NaFe 0.7 Nb 0.01 Mg 0.01 (PO4) 0.5 (P2O7) 0.25 (TiO3) 0.01 / BN@C]]> 8 0.1 96 88 98 Comparative Example 5 <![CDATA[NaFe 0.7 Nb 0.01 Mg 0.01 (PO4) 0.5 (P2O7) 0.25 (TiO3) 0.01 / BN@C]]> 2 0.5 95 82 80

[0098] According to the test results of Examples 1 to 9 and Comparative Examples 1 to 5, the cycle performance and rate performance of the battery when doped with elements such as Nb and Mg are relatively high. The doping of Nb elements can significantly reduce the internal resistance of the battery and improve the electrochemical properties of the positive electrode active material, especially the rate performance. Among them, according to Example 1 and Comparative Example 1, boron nitrogen doping can also improve the ionic and electronic conductivity of the material, which is of great significance to improving the rate performance and cycle performance. In addition, the fusion of metatitanate is also conducive to improving the cycle stability. According to Examples 1, 7 and Comparative Examples 1, 5, it can be seen that boron nitrogen doping can improve the electrochemical performance, but too high a ratio will have a negative effect. The imidazole heterocyclic complex is carbonized during the sintering process. At the same time, the boron nitrogen elements are hybridized with carbon during carbonization, which has better reducibility, can reduce the sintering temperature of the positive electrode active material, and is conducive to reducing the manufacturing cost. At the same time, if the boron nitrogen doping ratio is too high, the carbon material will be unevenly distributed on the surface of the active material, resulting in the battery capacity and rate being affected. The research results show that the mass ratio of boron nitrogen doping to the carbon coating layer should not exceed 0.2%. According to Examples 1, 2 and Comparative Example 4, when the carbon coating amount on the surface of the positive electrode active material is too high, although the cycle performance and rate performance of the battery are significantly improved, too much carbon coating reduces the proportion of active materials in the positive electrode material, and the discharge gram capacity of the positive electrode material is significantly reduced, which is not conducive to improving the energy density of the phosphate positive electrode material and reducing the battery cost. Therefore, calculated by mass fraction, it is best that the content of the boron-nitrogen-doped carbon layer coating layer on the surface of the composite phosphate positive electrode active material accounts for no more than 5% of the positive electrode active material, and the battery can obtain better discharge specific capacity, cycle performance and rate performance.

[0099] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A phosphoric acid-based positive electrode active material, characterized in that: The chemical general formula of the positive electrode active material is L a Fe x1 Nb x2 M x3 (PO4) y (P2O7) z (TiO3) e / BN@C, and the boron and nitrogen-doped carbon layer forms a conductive coating layer on the surface of L a Fe x1 Nb x2 M x3 (PO4) y (P2O7) z (TiO3) e ; where 0.5 < a ≤ 1.1, 0 < x1 < 1, 0 < x2 < 0.05, 0 < x3 < 1, 0 < y ≤ 1, 0 ≤ z ≤ 1, 0 < e ≤ 0.05, L is one or both of Na and Li, and M is one or more of Mn, Ni, V, Ti, Mg, Cu, Zn, Zr; calculated by mass fraction, the boron and nitrogen-doped carbon layer accounts for 1-5% of the positive electrode active material, and the boron and nitrogen element content accounts for 0.05-0.2% of the coating layer.

2. The positive electrode active material according to claim 1, characterized in that The positive electrode active material has the general chemical formula L a Fe x1 Nb x2 M x3 (PO4) y (P2O7) z (TiO3) e / BN@C, where 0.8 <a≤1,0<x1<1,0<x2<0.03,0<x3<0.8,0<y≤1,0≤z≤0.8,0<e≤0.05。 3. A method for preparing a positive electrode active material according to any one of claims 1 to 2, characterized in that: The preparation method comprises the following steps: S1. Sodium borohydride or lithium borohydride, a nitrogen-containing organic precursor and glucose are added to a flask, heated under reflux stirring at 100-250° C. for 1-5 h under nitrogen conditions, and cooled to room temperature to obtain a carbon source powder A; S2. Select several of carbon source powder A, L source compound, Fe source compound, M source compound, Nb source compound and phosphorus source compound as raw materials according to the product structure, and weigh appropriate amounts of the above raw materials for premixing to obtain premixed powder; S3, adding the premixed powder, solvent and dispersant into a nano sand mill for ball milling to obtain a slurry, wherein the primary particle size of the slurry is in the range of 100 to 400 nm; S4, spray-drying and granulating the slurry to obtain a precursor powder, and then pre-sintering the precursor powder under an inert atmosphere, and mixing it with sodium metatitanate or lithium metatitanate by double planetary mechanical ball milling after cooling, and sintering the mixed powder under an inert atmosphere, and cooling to obtain the boron-nitrogen-doped carbon-coated phosphate positive electrode active material L a Fe x1 Nb x2 M x3 (PO4) y (P2O7) z (TiO3) e / BN@C.

4. The preparation method according to claim 3, characterized in that: In step S2, the L source compound is selected from one or more of sodium carbonate, sodium hydroxide, sodium oxalate, sodium nitrate, lithium carbonate, lithium hydroxide, lithium oxalate, and lithium nitrate; the Fe source compound is selected from one or more of carbonates, oxides, nitrates, and oxalates; the M source compound is selected from one or more of carbonates, oxides, nitrates, and oxalates; the Nb source compound is selected from one or more of niobium pentoxide, niobium tetroxide, niobium trioxide, niobium oxide, niobium sulfide, niobium pentachloride, niobium tetrachloride, and niobium nitride; the phosphorus source compound is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; the nitrogen-containing organic precursor is selected from one or more of 2-methylimidazole, 2-ethylimidazole, 3-propylimidazole, and imidazole.

5. The preparation method according to claim 3, characterized in that: In step S3, the dispersant is selected from one or more of ammonium polyacrylate, polyvinyl pyrrolidone, and polyethylene glycol; the solvent is deionized water; the mass ratio of the premixed powder to the solvent is 1:(2-5); the mass of the dispersant is 0.1-2% of the mass of the solvent; and the ball milling time is 5-15 hours.

6. The preparation method according to claim 3, characterized in that: In step S4, the particle size of the sodium metatitanate or lithium metatitanate is 0.2~0.6µm; the pre-sintering temperature is 300~400°C, and the sintering time is 1~3h; the sintering temperature is 500~800°C, and the sintering time is 5~15h; the inert atmosphere is nitrogen or argon.

7. A positive electrode plate for a battery, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 2 or the positive electrode active material obtained by the preparation method according to any one of claims 3 to 6.

8. A sodium ion battery or a lithium ion battery, characterized in that: The sodium ion battery or lithium ion battery comprises a positive electrode sheet, a negative electrode sheet and a separator separated between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet is the positive electrode sheet according to claim 7.

Citation Information

Patent Citations

  • A multi-component doped lithium phosphate cathode material and its preparation method, and a lithium-ion power battery

    CN102290576A

  • High-conductivity lithium iron phosphate material and its making technology

    CN102487140A

  • Method for preparing titanium-doped lithium iron phosphate by taking synthetic rutile mother liquor as raw material

    CN116692815A

  • Modified phosphate positive electrode material as well as preparation method and application thereof

    CN118899436A